THE INFLUENCE OF SELF-EFFICACY ON STUDENT LEARNING OUTCOMES WITH ENVIRONMENT AS A MODERATING VARIABLE - Fauzi Farchan; Taransa Agasya Tutupoly; Krisna Mediyantoro Baharuddin; Gabriel Amadeus Sitompul; Andy Soenanta (Adisam Publisher, 2025)
This research is a quantitative research with an explanatory approach. The data used in this study are primary data from interviews with 400 high school students spread throughout Indonesia. The interview consisted of 10 questions with three main teams around Self-Efficacy, Student Learning Outcomes, and School Environment. The interview content contained 5 statements, namely strongly agree, agree, normal/so-so, disagree, and strongly disagree. The data was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that each hypothesis proposed by the researcher in the research methodology section can be accepted. In the first hypothesis section which is in line with the five previous studies, namely (Revita 2019); (Pertiwi 2021); (NURLATIFAH RANGKUTI 2021); (Hartini 2023) & (Faadhilah 2020)shows similar results, namely the Self-Efficacy variable can have a positive relationship direction and a significant influence on Student Learning Outcomes because the P-Values are positive and below the significance level of 0.05, namely 0.023. This is because self-efficacy can create self-confidence or potential, competitive ability, and other things that can improve student learning outcomes. In the second hypothesis, as well as proof of the researcher's creativity in adding the Environment variable as a moderating variable, it also shows similar results, namely the Environment variable can moderate the influence of the Self-Efficacy variable on Student Learning Outcomes. This is because the P-Values value leads to the positivity and is below the significance level of 0.05, which is 0.000, which is more significant than direct testing of 0.023. Thus, the first and second hypotheses in this article can be accepted and proven.